PENGARUH IMPLEMENTASI KEBIJAKAN PROTOKOL KESEHATAN TERHADAP PENURUNAN KEJADIAN COVID-19 - Dewi - Sayati (Masker Medika, 2022)
Background : One of the challenges in handling Covid-19 is that there are people who are against government policies. Some of these people still don't believe in the Covid-19 virus, distrust the information and reality about Covid-19 that the government provides, and not complying with government policies, including the implementation of health protocols. According to data from the Center for Systems Science and Engineering (CSSE) at Johns Hopkins University (JHU), Indonesia is in the top 20 list in the world. To be precise, it is in the 18th position, with the number of cases reaching 1,837,126 (as of June 24, 2021), and the death toll reaching 51,059 people. Methods: The research design is a descriptive quantitative survey with a cross sectional approach and the sampling technique used is accidental sampling and a sample of 71 respondents, which was then performed a chi-square statistical test, with a confidence degree of 95%. Results: The results of the statistical test show that there is a relationship between communication (p value 0.003), attitude (p value 0.001), and attitude of the implementer (p value 0.004) with a decrease in the number of cases of covid-19.